The Flipped Classroom Model in Learning Grammar: Students' Responses - Amanda Amanda; Fauzi Miftakh; Yousef Bani Ahmad (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
The aim of this study focusses on the use of flipped classroom model in grammar learning: students’ responses. This study used a qualitative approach and case study as a research design. This research took place in one of junior high school at Klari, Karawang. The participants of this study were an EFL Teacher and six seventh grade students. This research used observation and interview as data collection technique. The observation was conducted in three times. For the interview session, the researcher interviewed six students where these students were two people who had low level, two people who had intermediate level and two people who had high level in English. The findings of the research showed that the use of flipped classroom model in grammar learning has 3 activity phases, namely before the class, in class, and post class activity. In addition, the findings of this research showed that students’ responses towards the use of the flipped classroom model in learning grammar are positive. The students’ responses are presented into four categories, namely flipped classroom makes grammar learning easier, flipped classroom makes students more active in the class, flipped classroom stimulating students' autonomous learning, and flipped classroom makes grammar learning interesting. Key words: Flipped Classroom Model; Grammar; Students’ Responses